Early vision impairs tactile perception in the blind. - Röder, B; Rösler, F; Spence, C (2004)
Researchers have known for more than a century that crossing the hands can impair both tactile perception and the execution of appropriate finger movements. Sighted people find it more difficult to judge the temporal order when two tactile stimuli, one applied to either hand, are presented and their hands are crossed over the midline as compared to when they adopt a more typical uncrossed-hands posture. It has been argued that because of the dominant role of vision in motor planning and execution, tactile stimuli are remapped into externally defined coordinates (predominantly determined by visual inputs) that takes longer to achieve when external and body-centered codes (determined primarily by somatosensory/proprioceptive inputs) are in conflict and that involves both multisensory parietal and visual cortex. Here, we show that the performance of late, but not of congenitally, blind people was impaired by crossing the hands. Moreover, we provide the first empirical evidence for superior temporal order judgments (TOJs) for tactile stimuli in the congenitally blind. These findings suggest a critical role of childhood vision in modulating the perception of touch that may arise from the emergence of specific crossmodal links during development.